Transformations in the Caucasus: Cultural interactions and movements of people from the Neolithic to the Early Bronze Age - Lyonnet, Bertille (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
Based upon archaeological data and the first results of genomic studies, the article aims at understanding the successive cultural transformations at work in the Caucasus area (North and South) and along the Euphrates, starting from the Neolithic period up to the beginning of the 3rd millennium BCE. Long lasting cultural interactions with northern Mesopotamia are observed from the Neolithic to the middle of the 4th millennium. Questions are raised concerning the introduction of the black (and red) polished pottery during the 4th millennium that led to the formation of the Kura-Araxes and Novosvobodnaja cultures. Other questions concern the rich cist-burials that appear mainly on a North-South axis along the Euphrates at the end of that millennium. Although many changes and developments can be explained by the circulation of small groups of people coming from the same original genomic pool for trade and exchange, the intrusion of small alien groups from Central Europe seems possible in the second half of the 4th millennium.